Fractional Variational Iteration Method and Its Application to Fractional Partial Differential Equation - Elbeleze, AA; Kilicman, A; Taib, BM (Hindawi Publishing Corporation, 2024)
We use the fractional variational iteration method (FVIM) with modified Riemann-Liouville derivative to solve some equations in fluid mechanics and in financial models. The fractional derivatives are described in Riemann-Liouville sense. To show the efficiency of the considered method, some examples that include the fractional Klein-Gordon equation, fractional Burgers equation, and fractional Black-Scholes equation are investigated.